Finite Time Prescribed Performance Control for Uncertain Second-Order Nonlinear Systems - Hui Lv; Wei Xiang; Jun Zhu (Journal of Mathematics)
In this article, we discuss the finite time stability problem for second-order systems with an uncertain nonlinear function. A finite time performance function with the sinusoidal function is constructed, and the constrained problem of the original system is transformed into the stability problem of the equivalent system. Combining prescribed performance control and fuzzy logic systems, an effective control method is proposed. The simulation results also prove that the method we adopted is effective.